Empowering the learning community of junior high school teachers in the Sukaraja sector to implement the Merdeka curriculum - Selviani, Diah; Suwarni, Suwarni; Suranti, Dewi; Kurnianto, Ridho Rahman; Lestari, Monica Indah; Andika, Miki (Universitas Muhammadiyah Magelang, 2025)
The Merdeka curriculum is a curriculum that, in its learning process, refers to an approach based on talents and interests. One way to implement the Merdeka curriculum effectively is by optimizing learning communities within educational institutions. However, teachers face challenges in applying differentiated learning. This community service activity aims to enhance the knowledge and competencies of the learning community of junior high school teachers in the Sukaraja sector in implementing the Merdeka curriculum through the utilization of digital-based technology. The method used consists of three stages: preparation, workshop implementation, and evaluation. The results indicate that 86% of teachers experienced an increase in understanding and knowledge, 87% acquired new skills, and 75% produced high-quality outputs. This demonstrates that the empowerment activities significantly contributed to improving teachers' skills in implementing the Merdeka curriculum through digital-based technology utilization.